 Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping ```Solved Examples on Differentiation

Example 1: i. lim (x→0) (tan x-sin x) / x3

ii. lim (x→0) (a2-b2)/x

iii. lim (h→0) log (x+h) – log x/(x3h)

Solution:

The given question can be solved by two methods. We discuss both the methods one by one:

Method 1:

i. lim (x→0) (tan x – sin x)/x3 [0/0 form]

Differentiate denominator and numerator separately (i,e, apply L' Hospital rule)

= lim (x→0) (sec2x – cos x)/3x2 [0/0 form]

Again applying L' Hospital Rule

= lim (x→0) (2 sec x sec x tan x + sin x )/(6x) [0/0 form]

applying L' Hospital Rule again

= lim (x→0) (2 sec4x + 4 tan2x sec2x + cos x)/(6)

= (2+1)/6

= 1/2

Method 2:

Alternatively, we can also solve the above question in the following way

(tan x – sin x)/x3 = (sin x (1 – cos x))/cos x . x3

sin x / x. 2 (sin2 (x/2)/(x/2)2).1/4

= 1/2 Note:

Many of the problems can be solved with or without using L'Hospital rule.However you should always try to solve a problem without using L' Hospital's Rule.

ii. lim (x→0) (ax - bx)/x (0/0 form)

Using L' Hospital rule

= lim (x→0) (ax logea – bx logeb)/1

= logea- logeb

= loge(a/b)

iii. lim (h→0) log (x + h) – log x/h (0/0 form)

Applying L' Hospital Rule

lim (h→0) (1/(x + h) – 0)/1 = 1/x [differentiating numerator and denominator with respect to h]

___________________________________________________________________________

Example 2:

(i) If g(x) = -√(25 - x2) find lim (x→1) (g(x) – g(1))/(x-1)

(ii) Find value of a, b, c so that lim (x→0) (aex - b cos x + ce(-x))/(x sin x) = 2

Solution:

(i) lim (x→1) (g(x) – g(1))/(x-1)

= lim (x→1) g'(x) - g'(1)

But, g' (x) = -1/(2√(25 – x2)) (-2x)

⇒ g' (1) = 1/√24

(ii) lim (x→0) (aex - b cos x + ce(-x))/(x sin x) = 2

Let f(x) = aex - b cos x + ce- x

And g(x) = x sin x

lim (x→0) g(x) = 0

lim (x→0) (aex -b cos x + ce(-x))/(x sin x) = 2

So, f(x) should be zero for finite limit of f(x)/g(x)

⇒ a + c = b ....... (i)

⇒ L = lim (x→0) (aex - b cos x + ce(-x))/(x sin x) [0/0 form]

Again using L' Hospital's Rule

= lim (x→0) (aex + b sin x - ce(-x))/(x cos x + sin x)

Denominator = lim (x→0) x cos x + sin x = 0

So for finite, lim (x→0) aex + b sin x – ce(-x) = 0

⇒ a - c = 0

a = c ........ (ii)

L = lim (x→0) (aex + (2a) sin x – ae(-x))/(x cos x + sin x ) [0/0 form] (using (i) and (ii))

= lim (x→0) (a(ex + e(-x)) + 2a cos x)/(-x sin x + 2 cos x) (applying L' Hospital rule)

= lim (x→0) (a(ex + e(-x)) + 2a cos x)/(-x sin x + 2 cos x)

= (2a + 2a)/2

= 2a

Given the value of limit is 2

Hence 2a = 2

⇒ a = 1

⇒ c = a = 1 (from equation (ii))

⇒ b = a + c = 1 + 1 = 2 (from equation (i))

⇒ a = 1, b = 2, c = 1.

___________________________________________________________________________

Example 3:

Find differential coefficient of 'y' with respect to 'x'.

1. y = 1/log cos x

2. 8x/x8

3. y = tan-1(√(1 + x2 - x))

Solution:

(i) y = 1/log cos x

Let log cos x = μ

y = 1/μ (differentiating w.r.t. μ)

dy/dμ = – 1/μ2

μ = log cos x

Let cos x = t

dμ/dt = 1/t

dμ/dx = dμ/dt. dt/dx

= 1/t (-sin x) = sin x/cos x

= -tan x

dy/dx = dy/dμ.dμ/ dx

= -1/μ2 (-tan x)

= tan x/(log cos x)2

Method 2:

y = (log cos x)-1

dy/dx = (-1) (log cos x)(-1-1). d/dx (log cos x)

= (-1)/(log cos x)2 × 1/cos x × d/dx(cos x)

= (-1)/(log cos x)2.1/cos x (-sin x)

= tan x / (log cos x)2 Note:

Chain rule has been applied in the above question.

(2) y = 8x/x8

Taking loge on both side

log y = log 8x - log x8

log y = x log 8 - 8 log x

Differentiating w.r.t. x

1/y dy/dx = log8 – 8/x

dy/dx = 8x/x8 [log 8 – 8/x ]

dy/dx = 8x/(x9) [x log 8 - 8]

(3) y = tan-1(√(1 + x2- x))

Subtracting x = tan θ

y = tan-1(√(1 + x2 - θ) – tan θ)

= tan-1(sec θ – tan θ)

= tan-1((1 - cos (π/2-θ))/sin (π/2-θ))

= tan-1(tan 1/2 (π/2-θ))

= π/4 – 0/2 y

= π/2-1/2 tan-1x; by putting the value of θ

Differentiating w.r.t. x, we get

dy/dx = -1/(2(1 + x2))

_______________________________________________________________________

Example 4:

lim (x→0) sin (π cos2x)/ x2 equals (IIT JEE 2001)

(a) – π                                                                        (b) π

(c)  π/2                                                                       (d) 1

Solution:

lim (x→0) sin (π cos2x)/ x2

= lim (x→0) sin (π – π sin2x)/ x2

=  lim (x→0) sin (π sin2x)/ (π sin2x) . (π sin2x)/(πx2) . π

= 1.1.π

= π

____________________________________________________________________________

Example 5:

If y is a function of x and log(x + y) = 2xy, then the value of y’(0) = ? (IIT JEE 2004)

(a) 1                                                                        (b) -1

(c) 2                                                                        (d) 0

Solution:

Gievn that log (x + y) = 2xy

Hence, at x = 0 we have log (y) = 0

This gives y = 1.

Now, to find dy/dx at (0, 1),

On differentiating the given equation with respect to x we have,

1/(x+y) . (1+ dy/dx) = 2x dy/dx + 2y.1

Hence, dy/dx = [2y(x + y) – 1]/[1-2(x + y)x]

So, (dy/dx)|(0,1) = 1.

________________________________________________________________________

Example 6:

If 2x + 2y = 2x+y then dy/dx has the value equal to

(a) -2y/2x                                                                       (b) 1/(1 – 2x)

(c) 1 – 2y                                                                        (d) 2x/2y (1 – 2y)/(2x -1)

Solution:

The given function is 2x + 2y = 2x+y

Differentiating both sides we get

2x ln 2 + 2y ln 2 dy/dx = 2x+y ln 2 (1 + dy/dx)

Hence, dy/dx ( 2x+y - 2y) = 2x - 2x+y

This gives dy/dx = -2y/2x

_____________________________________________________________________

Example 7:

Find the derivative of

1. log7(log7x).

2. y = cos-1[(2 cos x + 3 sin x)/√13]

Solution:

(i) y = log7(log7x)

log7x = (logex)/(loge7)

Caution: Since all results in differentiation are to the base 'e'

log7 [(logex)/(loge7)] = loge[(logex)/(loge7)] / (loge7)

(loge7) is treated as constant with respect to x.

dy/dx  = 1/ (loge7) . [1/(logex) . 1/x]

dy/dx  = 1/ (loge7). x .logex

(ii) y = cos-1[(2 cos x + 3 sin x)/√13]

= cos-1 [2/√13 cos x + 3/√13 sin x] where 2/√13 = cos θ and 3/√13 = sin θ

= cos-1 [cos θ cos x + sin θ sin x]

= cos-1[cos (x – θ)]

Result: We know that cos-1 (cos x) = x]

Hence, we have y = x - θ ; θ is a constant w.r.t 'x'

dy/dx = 1 - 0 = 1. Note:

This example shows the significance of simplification in solving problems. If our approache had been to differentiate directly we would have never been able to get the result so quickly. Remember your approach should always be toward getting quick and correct results.

_____________________________________________________________________

Example 8:

If y = x log (x /(a + bx)), then show that x3(d2y)/(dx2) = [x dy/dx - y]2.

Solution:

Method 1:

y = x log x – x log (a + bx)

dy/dx = x/x + 1.log x – x(b)/(a + bx) -1.log (a + bx)

= 1 - bx/(a + bx) + log x - log (a + bx)

dy/dx = a/(a + bx) + y/x (using the given condition)

x dy/dx = ax/(a + bx) + y ........ (i)

x.(d2y)/(dx2) + 1.dy/dx = a[((a + bx) - x(b))/(a + bx)2] + dy/dx

= a2/(a + bx)2

= [(x dy/dx – y)/x]2 from equation (i)

x3(d2y)/(dx2) = [x dy/dx - y]2  (Hence Proved) Note: It is important to note the simplification of the form of dy/dx without which proof would have not been that easy.

Method 2:

y/x = log x – log (a + bx)

Differentiating with respect to x, we get

y/x = log x – log(a + bx)

Differentiating w.r.t. x

(xy' – y)/x2 = 1/x – b/(a + bx)

= a / (x(a + bx))

⇒ xy' - y = ax/(a + bx)

Differentiating w.r.t. x again, we get

xy" + y' - y' = (a/(a + bx))2

⇒ xy" = ((xy' – y)/ x)2(using (i))

⇒ x3y" = (xy'-y)2. Hence proved.

Related Resources:

You may wish to refer Differentiation.

For getting an idea of the type of questions asked, refer the previous year papers.

To read more, Buy study materials of Methods of Differentiation comprising study notes, revision notes, video lectures, previous year solved questions etc. Also browse for more study materials on Mathematics here.
```  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution 